Study on The Effect of Cold-Rolling and Subsequence Welding on the Corrosion Rate of 304L - Niko Arianto; Suwarno Suwarno (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2019)
Corrosion is an event of material damage due to reacting chemically with the environment. Stainless steel is a widely used steel in the industrial world, for example, the austenitic stainless-steel type 304L. The problem that still arises with 304L stainless steel is corrosion at grain boundaries. The sensitization process occurs when the steel is heated at a temperature of 500◦C – 700◦C resulting in chromium carbide precipitation formation. Sensitization of austenitic stainless steel can occur during the welding process, which can cause damage to the heat-affected zone (HAZ). Cold working on metals is a deformation process that is carried out at temperatures below the recrystallization temperature. This research was conducted to determine the effect of variations in rolling and welding. Rolling was carried out using a cold working process with a variation of the workpiece reduction, namely 20%, 40%, and 60%. Welding was carried out with current variations of 50, 65, and 80 with a welding time of 5 s and 10 s. The corrosion rate was tested using a potentiostat to obtain current density (Icorr) and potential (Ecorr) data. From the research, it was found the relation between rolling, welding parameters, and the corrosion rate. The corrosion rate is controlled by the carbide precipitation in the HAZ regime.